2014
DOI: 10.1186/s13058-014-0486-7
|View full text |Cite
|
Sign up to set email alerts
|

E2F4 regulatory program predicts patient survival prognosis in breast cancer

Abstract: IntroductionGenetic and molecular signatures have been incorporated into cancer prognosis prediction and treatment decisions with good success over the past decade. Clinically, these signatures are usually used in early-stage cancers to evaluate whether they require adjuvant therapy following surgical resection. A molecular signature that is prognostic across more clinical contexts would be a useful addition to current signatures.MethodsWe defined a signature for the ubiquitous tissue factor, E2F4, based on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 57 publications
8
51
0
Order By: Relevance
“…We have previously developed a method to identify transcriptional regulatory programs that are predictive of cancer prognosis (29, 30). A regulatory program consists of transcription factors and its target genes identified by ChIP-chip or ChIP-seq experiments (31, 32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously developed a method to identify transcriptional regulatory programs that are predictive of cancer prognosis (29, 30). A regulatory program consists of transcription factors and its target genes identified by ChIP-chip or ChIP-seq experiments (31, 32).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to multigene prognostic signatures identified by supervised models, regulatory programs are defined on the basis of prior knowledge learned from ChIP-seq/chip data. We have previously identified an E2F4 regulatory program that showed robust power in predicting the survival of breast cancer patients (29). E2F4 is a member of the E2F transcription factor family, which plays critical roles in cell-cycle progression and differentiation (34).…”
Section: Introductionmentioning
confidence: 99%
“…We and other researchers have shown the prognostic value of E2F4 in breast cancer (21, 39) and bladder cancer (40). Molina-Privado et al have investigated its function in Burkitt lymphoma tumorigenesis, and found reduced protein but not mRNA levels of E2F4 in sporadic Burkitt lymphoma cell lines and tumor samples (41).…”
Section: Discussionmentioning
confidence: 69%
“…We have previously developed computational methods, REACTIN (Regulatory Activity Inference) and BASE (Binding Association with Sorted Expression), to investigate the regulatory programs associated with cancer (19-21). Both of the methods integrate gene expression data with ChIP-seq transcription factor (TF) binding data with the rationale that the regulatory activity of TFs can be reflected by the expression of their target genes.…”
Section: Introductionmentioning
confidence: 99%
“…REPA's predictions associated 58 TFs with the gene sets identified as differentially expressed in the breast cancer expression profiling study. Out of these 58 TFs, 50 (or 86%) have previously been directly linked to breast cancer; namely, AP2ALPHA [85], AP2GAMMA [85], ATF1 [86], ATF2 [87], ATF3 [88], BAF155 [89], BCL3 [90], BCLAF1 [91], BHLHE40 [92], [93], BRCA1 [94], CBX3 [95], CEBPB [96], CJUN [97], COREST [98], CREB1 [99], E2F4 [100], E2F6 [61], EBF [101], ELF1 [102], ELK1 [103], ETS1 [104], FOXM1 [105], GABP [106], GR [107], HEY1 [108], IKZF1 [109], INI1 [110], KAP1 [111], MAX [112], MBD4 [113], MTA3 [114], MXI1 [115], MYBL2 [116], NFATC1 [117], NFIC [118], NRSF [119], PAX5 [120], PML [121], POL2 [122] RUNX3 [123], SMC3 [124], SP1 [125], SP4 [126], STAT3 [127], STAT5A …”
Section: Differentially Expressed Gene Sets Repa's Predicted Putativementioning
confidence: 99%